¿Impuesto a la riqueza en el Perú? Reflexiones sobre su posible re–incorporación al sistema tributario peruano - Morales Gamarra, Michael Fernando (2021)
In this article, the authors analyse the nature of the wealth tax, its history in the Peruvian tax system, how it has been applied in different jurisdictions and several legislative initiatives introduced to the Congress of Peru.